UCL23 hierarchically regulated by WRKY51-miR528 mediates cadmium uptake, tolerance, and accumulation in rice - Jingai Tan; Lantian Zhang; Chuanjia Liu; Zheyuan Hong; Xia Wu; Yaqi Zhang; Muhammad Fahad; Yuxin Shen; Jianmin Bian; Haohua He; Dezhi Wu; Qingyao Shu; et al. (Cell Reports)
Summary: In humans, cadmium (Cd) toxicity caused by contaminated environments is associated with numerous chronic diseases. Breeding rice with low Cd accumulation is now deemed critical for sustainable agriculture development. Here, we elucidate the crucial functions of UCLACYANIN 23 (UCL23), a small copper protein, in Cd absorption, tolerance, and accumulation through modulation of reactive oxygen signals in rice. Additionally, we demonstrate that WRKY51 binds to promoters of UCL23 and miR528, a post-transcriptional regulator of UCL23, thereby contributing to Cd regulation in a dual-modulatory manner. Furthermore, we show that the natural variation of UCL23 is important for the differential accumulation of Cd in rice grains. Finally, we reveal that Indica rice harboring the major Japonica haplotype of UCL23 significantly reduces Cd uptake in roots and Cd accumulation in grains. Together, our study not only reveals a regulatory cascade in Cd regulation but also provides valuable resources for breeding low-Cd rice cultivars.